EFFECTIVENESS OF THE SOCIAL INQUIRY METHOD IN ENHANCING CRITICAL THINKING SKILLS AMONG SCHOOL STUDENTS - Katgeri, Archana V; Khan, Sumaiya (International Journal of Research -GRANTHAALAYAH, 2025)
This study explores the effectiveness of the Social Inquiry Method (SIM) in enhancing critical thinking skills among 8th-grade students. Employing a single-group experimental research design, the study engaged students over six sessions, were inquiry-based method was used in contemporary social issues such as cyberbullying, social media and mental health, environmental concerns, artificial intelligence, gender equality, and access to education. Observational data indicated significant improvements in students’ engagement, analytical reasoning, empathy, and collaborative learning. The SIM's structured phases—orientation, hypothesis formulation, definition, exploration, and generalisation enabled students to actively construct knowledge, evaluate multiple perspectives, and propose creative solutions to complex issues. Findings suggest that the Social Inquiry Method not only strengthens students’ critical thinking but also fosters meaningful, student-centred learning aligned with real-world challenges. The study recommends the broader integration of SIM into middle school curricula to promote intellectual autonomy, reflective thinking, and social consciousness among learners.